Global Experiences of Community Responses to COVID-19: A Systematic Literature Review - Wu, Yijin; Zhang, Quan; Li, Meiyu; Mao, Qingduo; Li, Linzi (Frontiers in Public Health, 2022)
Objective: The aim of this study was to conduct a systematic review of the global experiences of community responses to COVID-19 epidemic. Method: Five electronic databases (PubMed, EMBASE, CINAHL, ScienceDirect, and Web of Science) were searched for peer-reviewed papers published in English, from inception to October 10, 2021. Two reviewers independently reviewed titles, abstracts and full texts. A systematic review (with a scientific strategy for literature search and selection in the electronic databases applied to data collection) was used to investigate the experiences of the residential community responses to COVID-19 pandemic. Results: In this review, it has been identified that community responses consist mainly of three aspects: community screening for the virus, cutting off the transmission chain of the virus, and providing medical aid for mild cases. In addition, social support for the residents, including material, educational and psychosocial support, were used to balance epidemic control and prevention and its impact on residents’ lives. Moreover, special care was provided to vulnerable residents during the epidemic. Conclusion: This review shed some light on communities which are still overwhelmed by COVID-19 pandmic and provdie valuable experiences for community responses to future pandemics.